Mathematics of evolution and phylogeny - Gascuel, Olivier, 1956- (New York : Oxford University Press, 2005)
"This book considers evolution at different scales. The focus is on the mathematical and computational tools and concepts, which form an essential basis of evolutionary studies, indicate their limitations, and give them orientation"--Provided by publisher.
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2023. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Evolution (Biology) -- Mathematics; Phylogeny -- Mathematics; Electronic books